(untitled) (Research, Society and Development, 2022)
The hospital psychologist in the face of perinatal loss is necessary by providing a space for the bereaved mother to express her pain and understand her feelings and thus be able to resignify the mourning for the loss of her child, since it is a delicate and painful process that in many cases is neglected, and pregnancy is characterized as a time of happiness and full of expectations and dreams. Its general objective is to investigate the role of the hospital psychologist in the mental health care of women during the process of perinatal mourning. This is an integrative literature research with a quantitative approach. The inclusion criteria used were the studies that address the theme and those consistent with the objective of this study. The exclusion criteria were those that did not address the theme in question and were not part of the triad of studies in the scope: hospital psychology, perinatal mourning, and women’s mental health. Furthermore, those without precise results were excluded, as well as theses, dissertations, Course Completion Papers, congress annals, and published abstracts. The results obtained demonstrate the importance of the hospital psychologist in the process of perinatal mourning, offering this woman a space to listen, express and understand her feelings and her pain, so that she can elaborate the mourning for the lost child.